A Cross-Sectional Study on Mean Perception of Pain after Mini-Screw Placement among Patients Seeking Orthodontic Treatment - Waheed Gul Shaikh, Anum Tariq, Qasim Khalid, Madiha Rasheed, Muhammad Yousaf Ali, Sameer Quraeshi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The orthodontist and patients prefer the usage of mini-screw anchorage due to its feasibility of insertion and removal, which necessitates minimum patient cooperation, and cost-effectiveness. Aim: The aim of the study is to access the mean perception of pain using a visual analogue scale after placing the mini-screws in orthodontic patients. Methods: Using convenient sampling technique, this cross-sectional study was held at Armed Forces Institute of dentistry, Rawalpindi and Shahida Islam Dental College, Lodhran for six-months duration from July 2022 to December 2022. A total of 80 patients took part in the study. On a 10-millimeter visual analogue scale (VAS), where 10 signifies "the severe pain presumable" and 0 signifies "no pain," they were asked to rate their anticipated level of pain Results: A total of 80 patients were selected for this study with the mean age of 21.1± 2.8. The majority of subjects (60%) were female, and the posterior maxilla (48.8%) and posterior mandible (30%) were mostly implanted with mini-screws. Mostly, patients described pain on the 1st day of mini-screws insertion with mean VAS was 4.10± 1.65 and on 7th day; minimum pain was experienced with VAS of 2.9±1.09. There was a significant variation (p ≤0.01) in the VAS score between the sexes, with women exhibiting a higher VAS score (39 ± 52.7) compared to men (35 ± 47.3). Conclusion: Mini screws can more precisely carry out difficult tooth movements than the traditional anchorage used in standard orthodontic treatment. Keywords: Pain, mini-screws placement, mean pain perception and visual analogue scale.